ANALISIS CAPAIAN LITERASI SAINS BIOLOGI SISWA SMA KELAS X SEKOTA PADANG - Fadhilatul Huryah; Ramadhan Sumarmin; Jon Effendi (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2017)
Based on the results of PISA in 2000- 2009, the score of Indonesian students' science literacy with the average score was 500. The low score of Indonesian students’ acquisition is reflecting the poor performance of Indonesian students in learning science. This study was conducted to determine the students’ achievements of biological science literacy as the total score, science competency, content, context and problems format, and the description of scientific literacy PISA comparison with students’ origin school and the students’ National Examination result and the factors that influence it.This research is a descriptive research. It was conducted to student grade X in SMAN 1, SMAN 8, SMAN 13 and SMAN 16 Padang. The instrument used to collect data is the text about the biological scientific literacy PISA test taken from the book Take the Test: Sample Question from the OECD's PISA Assessment. The results showed that the highest score of biological science literacy based on the total score was obtained by the students of SMAN 1 score 57.50, SMAN 8 score 45.90, SMAN 13 score 43.50 and SMA 16 score 42.40. Based on the science competency, the students are good at applying scientific evidence. The overall score of the students’ science competency 48.51 (low), content t 48.12 (low) and context 46.82 (low) and the highest average score is in essay problem. It can conclude that the student of grade X, Senior High School in Padang have low point of students' science literacy